Below the parapet wall - beautifully carved miniature towers; Carving on the parapet wall - sequences from the epic Ramayana - Kishkinda kanda - Rama's meeting with Sugreeva - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] Parapet wall carving - Ramayana sequences from left to right. (1)Rama meets Sugreeva with his monkey army (2) Sugreeva hands him the ornaments Seeta has thrown down while Raana abducts her (3) Rama shoots through seven trees with one arrow to prove his prowess to Sugreeva. (4) Rama shoots an arrow from behind on Vali while Vali and Sugreeva fight (5) Sugreeva is coronated as the King of Kishkindha (6) Rama blesses Anagada or Hanuman (unclear) (7) Sugreeva's monkey army builds a stone bridge to Lanka with (8) Ravana's brother Vibheeshana approaches Rama for truce.